2018
DOI: 10.1128/mbio.00943-18
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous and Flexible Transmission of mcr-1 in Hospital-Associated Escherichia coli

Abstract: The recent emergence of a transferable colistin resistance mechanism, MCR-1, has gained global attention because of its threat to clinical treatment of infections caused by multidrug-resistant Gram-negative bacteria. However, the possible transmission route of mcr-1 among Enterobacteriaceae species in clinical settings is largely unknown. Here, we present a comprehensive genomic analysis of Escherichia coli isolates collected in a hospital in Hangzhou, China. We found that mcr-1-carrying isolates from clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 69 publications
4
29
1
Order By: Relevance
“…In addition, the mcr-1 positive isolates showed higher resistance to PB than the mcr-1 negative E. coli isolates in this study, which suggested that there was a close positive correlation between the resistance phenotypes and genotypes of the mcr-1 positive isolates. This result is consistent with other reports (Huang et al, 2017;Shen et al, 2018;Zhuge et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the mcr-1 positive isolates showed higher resistance to PB than the mcr-1 negative E. coli isolates in this study, which suggested that there was a close positive correlation between the resistance phenotypes and genotypes of the mcr-1 positive isolates. This result is consistent with other reports (Huang et al, 2017;Shen et al, 2018;Zhuge et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with a recent report that the insertion of IS Kpn26 to the upstream of mcr-1 in E . coli isolates ZJ148 and ZJ1653 did not affect the colistin resistance ( Shen et al, 2018 ). We then reasoned that the host strain 14EC047 might suppress the activity of MCR-1.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic tree was generated using RAxML v.7.8.6. with 1,000 bootstraps (Kallonen et al, ; Shen, Wu, et al, ). MLST analysis was performed to define the MCRPEC ST‐types using the Warwick MLST scheme (Wirth et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the extensive use of antibiotics in human disease treatment, antimicrobial consumption in global animal farming, especially extensively subtherapeutic‐dose addition in animal feed, is a very important reason for the rapid dissemination of antibiotic‐resistant Enterobacteriaceae (Johnson et al, ; Liu et al, ). Polymyxins have been regarded as a final line of antimicrobial agents against the serious infections caused by MDR bacteria, such as clinically CRE (Shen, Wu, et al, ). However, this last‐line antibiotic has been challenged by the emerging and global transmission of plasmid‐encoded mcr genes.…”
Section: Introductionmentioning
confidence: 99%